Systematic review of surgical treatment of post radical prostatectomy stress urinary incontinence. Issue 8 (23rd September 2015) - Crivellaro, Simone; Morlacco, Alessandro; Bodo, Giovanni; Agro', Enrico Finazzi; Gozzi, Christian; Pistolesi, Donatella; Del Popolo, Giulio; Ficarra, Vincenzo
Abstract : Context Stress urinary incontinence (SUI) after radical prostatectomy (RP) continues to be a significant problem with several implications including patient quality of life and other critical postoperative outcomes. Objectives To report the results in terms of efficacy (pad count, 24 hr pad test, QOL questionnaires) and safety (complication rate and type of complications) of all surgical devices approved for the treatment of SUI after RP. Evidence Acquisition A systematic review was conducted in accordance with the PRISMA Statement. A literature search was carried out through the PubMed/Medline, SCOPUS, and Web of Science databases using the keywords "incontinence, " "radical prostatectomy, " and "'treatment". Inclusion criteria were: number of patients higher than 30, mean follow up longer than 12 months and definition of a successful outcome as the use of 0 to 1 safety pads a day. Evidence Synthesis 113 papers underwent primary review. 51 papers met the inclusion criteria with a total sample size of 4022 patients. Efficacy (0–1 safety pads) was on average 65.7% for AUS, 48.2% for Invance Sling, 48.8% for Advance Sling, 64.2% for ProACT. Twenty four hour pad test and QOL questionnaires were respectively available only in 4 and 18 studies. The overall complication rate was 19.43% for AUS, 7.4% for Invance Sling, 12.3% for Advance Sling, 12.3% for ProACT. Authors' Conclusions Due to the poor overall quality of available studies, it was impossible to identify or refute clinically important differences between the alternative surgical procedures. Although our data seems to suggest that AUS has the highest efficacy in the treatment of SUI following RP it is also associated with the highest complication rate, but this may be due to the longest follow up. Larger rigorous trials are needed in order to support this evidence. Neurourol. Urodynam. 35:875–881, 2016 . © 2015 Wiley Periodicals, Inc.